2022
DOI: 10.3233/jpd-223285
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Total Alpha-Synuclein (αSYN) Immunoassays Reveals That They Do Not Capture the Diversity of Modified αSYN Proteoforms

Abstract: Background: The development of therapeutics for Parkinson’s disease (PD) requires the establishment of biomarker assays to enable stratifying patients, monitoring disease progression, and assessing target engagement. Attempts to develop diagnostic assays based on detecting levels of the α-synuclein (αSYN) protein, a central player in the pathogenesis of PD, have yielded inconsistent results. Objective: To determine whether the three commercial kits that have been extensively used for total αSYN quantification … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 64 publications
(106 reference statements)
0
15
0
Order By: Relevance
“…Therefore, when additional aSyn PTMs are detected in LBs, it is plausible to assume that a significant percentage of aSyn within LBs bears multiple PTMs. Our results demonstrate that the presence of other PTMs in close proximity to pS129 dramatically influences antibody-based detection of monomeric 77 and aggregated forms of pS129-aSyn in a site, PTM type, and PTM number dependent manner. These findings, combined with increasing evidence demonstrating that aSyn aggregates bear multiple modifications and are enriched in C-terminally truncated species, suggest that it is unlikely that antibodies against pS129 or any single C-terminal (a.a. 115-140) targeting antibody are capable of capturing the diversity of aSyn species or aSyn pathology in the brain.…”
Section: Discussionmentioning
confidence: 78%
“…Therefore, when additional aSyn PTMs are detected in LBs, it is plausible to assume that a significant percentage of aSyn within LBs bears multiple PTMs. Our results demonstrate that the presence of other PTMs in close proximity to pS129 dramatically influences antibody-based detection of monomeric 77 and aggregated forms of pS129-aSyn in a site, PTM type, and PTM number dependent manner. These findings, combined with increasing evidence demonstrating that aSyn aggregates bear multiple modifications and are enriched in C-terminally truncated species, suggest that it is unlikely that antibodies against pS129 or any single C-terminal (a.a. 115-140) targeting antibody are capable of capturing the diversity of aSyn species or aSyn pathology in the brain.…”
Section: Discussionmentioning
confidence: 78%
“…While the relationship is conceptually intuitive, any significant relationship between the two measures would be expected to be of small effect size, given the aforementioned considerations related to measures of total aSyn by antibodies, whereby only a small percentage of the overall measure likely reflects pathologic forms of aSyn. 22 In addition, the SAA does not quantitate the absolute amount of pathologic aSyn, and we cannot exclude the possibility that there are pathologic components of total aSyn not amplified by the SAA. Our findings are, however, in contrast to Kang et al 26 as well as Poggiolini et al, 3 where even in a larger number of samples, a significant relationship between CSF aSyn and F max and/or T 50 was not found.…”
Section: Discussionmentioning
confidence: 98%
“…Further complicating the interpretation of total αSyn values is that while the full‐length protein is the most common form in the human body, there are at least three isoforms produced by alternative splicing. αSyn also undergoes several post‐translational modifications (PTMs), some of which are disease‐specific, 19 but are not measured by the assay applied to S4 specimens 22 . Another factor hampering the comparability of immunoassays are the antibodies used and the respective binding sites that leads to variability 18,22 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent comparative study demonstrated that three of the most commonly used immunoassays (ELISA) to measure total aSyn levels failed to detect the most disease-associated C-terminally truncated forms of aSyn. It showed that several N-terminal truncations and phosphorylation differentially influence aSyn detection and recovery by the three immunoassays 211 . Overall, the majority of published or commercially available immunoassays relied on antibodies that were not thoroughly validated, or the validation data were not reported.…”
Section: Introductionmentioning
confidence: 99%